ECONOMICS OF PIG PRODUCTION AMONG COOPERATIVE PIG FARMERS IN IJEBU-NORTH LOCAL GOVERNMENT AREA OF OGUN-STATE, NIGERIA - Nwankwo, F. O.; Jimoh, B. O.; Shittu, K. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study analysed economics of pig production among cooperative Pig farmers Ijebu-North Local Government Area of Ogun-State, Nigeria. A two-stage sampling technique was used for the study. Data were gathered using a well-structured questionnaire administered to seventy (70) respondents. Both descriptive and inferential statistics were used for the analysis. The results showed the mean age of the respondents was 36 years, majority (90%) of the respondents were males with an average of 6 persons per households. The result also indicated that majority (85.7%) of the respondents were married with an average of 13 years farming experience. Performance measures showed benefit-cost of 1.40, implied that for every ₦1.00 spent by the farmers on pig production, 40kobo was realised as profit. since, benefit-cost ratio exceeded 1. This indicated that pig production is economical, lucrative, viable and profitable enterprise.The results also revealed that inadequate credit facilities (100%) emerged as the most pressing concern and was ranked 1st, followed by weather conditions (96.7%) positioned 2nd, while inadequate market for piggery production. (65.0%) was least challenge ranked 12th. Therefore, study recommended solutions to the problems confronting pig farmers identified as follows; reduction of high price of drugs and vaccines, subsidizing or reduction of feed cost, provision of adequate funds, adequate and quality of breeding stock, provision of infrastuctural facilities and provision of adequate marketing of piggery production. If all identified solutions mentioned were all put into practice as agreed as solutions to the some challenges facing the farmers, the pig production will be easier and attractive likewise, farmer's income, profitability and production will be increased.